Autobiographical Biblical Criticism : Between Text and Self - Kitzberger, Ingrid R, (Deo Publishing, Religion and Theology Special E-Book Collection, 1999-2017, ISBN: 9789004401549., 2002)
The autobiographical turn in biblical criticism reveals the interpreter's "I" and reclaims it as an essential critical category, issuing a challenge to traditional, "objective" criticism. Pioneers in the field have contributed essays both practical and theoretical. They offer stimulating autobiographical re-readings of Hebrew Bible and New Testament texts, and address hermeneutical issues that are at stake in this young field of criticism.